Analisa Risiko Pekerjaan Overhaul Undercarriage PC210-10M0 dengan Metode Hazard Identification Risk Assessment Determining Control di PT Saptaindra Sejati Jobsite Sera - Jeryco Etwan Resha Putra; Erna Indriastiningsih; Agung Widiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
According to the circular letter from the Head of the Inspectorate General (KaIT) regarding the review of mining accident cases in September 2024 and the review of mining accidents in the third quarter of 2024, the percentage of accidents occurring in workshops reached 16.13%. Over the past five years, the Plant Department of PT Saptaindra Sejati Jobsite Sera has experienced two major incidents classified as Lost Time Injury (LTI) resulting from working with lifting equipment on undercarriage components. The purpose of this study is to identify risks, analyze risk levels, and provide recommendations for risk control in the overhaul work of the PC210-10M0 undercarriage. This research applies the HIRADC method by identifying potential hazards through calculations of likelihood and severity levels to obtain the risk level using a risk matrix. Control measures are then carried out through administrative actions such as documentation and the use of personal protective equipment (PPE). The results of this study indicate a decrease in risk levels after implementing risk controls—from extreme risk to medium risk, and from high risk to low risk. Suggestions from this study include the need to develop updated HIRADC for each section, actively conduct socialization regarding Job Safety Analysis (JSA) before work, and perform inspections as well as observations related to work behavior.